MERCATO CULTURALE: THE BIRTH OF A COLOSSEUM’S ORNAMENTATION - Oviedo Salazar, Mauricio (2015)
The Republic of Costa Rica, like many other Latin American nations during the XIX century, took the path to build a positive State based on liberal economic policies and a cultural program based on European models. The negotiations and contracts, mainly to Europe, made for the construction and decoration of the National Theatre of Costa Rica (1891-1897), were extremely complex. Certainly, the Minister Plenipotentiary Overseas Marquess Manuel María de Peralta y Alfaro played a key role in this project; however, the network of people involved was broader. Regarding the project of ornamentation and decoration of this building, we ask: How were carried out the relations between Italian merchants and the Costa Rican government? Through the revision of primary and secondary sources, using the hypothetical-deductive method, we were able to make an outline of trade and cultural relations of five Italian merchants, namely Francesco and Lorenzo Durini, Ruy Christóforo Molinari, Attilio Lazaro Riatti and Gaetano de Benedictis; with some Costa Rican citizens who acted as representatives of the State: Adolfo Erba, the Marquess of Peralta Ricardo Pacheco Marchena and Juan Jose Ulloa Giralt.